Green Materials in Traditional Housing: A Local Wisdom Lesson - Nurul Fakriah (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2015)
The consideration of sustainability, sustainable development, or sustainable future began to emerge in the beginning of 18th century, precisely after the Brundtland Commission Report had been published in 1987. In the beginning, environmental awareness rose in the industrial country such as European countries and America. It is the consequence of the industrial revolution which had caused negative impact to the environment. Furthermore, climate change and global warming have become a great issue. Buildings gave contribution in this issue due to their consuming energy and releasing emissions. Therefore, the use of appropriate material is a key point of green building. Some considerations of material selection for green building are resource efficiency, indoor air quality, energy efficiency, water conservation, and affordability. These aspects are analysed in traditional house’s materials. The result from this qualitative approach shows that the materials used in traditional houses are green. There are some lessons that can be drawn from this local wisdom. They could be very useful for the future design of buildings.